Peningkatan Motivasi Belajar Pak Dengan Model Pbl Materi Gereja Pada Fase F Kelas XI SMKN 3 Magelang - Didit Sugiyarso (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
There is a problem of a lack of motivation to learn and critical reasoning abilities in students in learning Catholic Religious Education and Characteristics in terms of competency achievement, students are able to understand the meaning and meaning of the Church in Phase F of Class XI SMKN 3 Magelang in the 2023/2024 academic year. So this research aims : Knowing the effectiveness of applying the PBL learning model in increasing motivation and critical reasoning skills in learning Catholic Religious Education and Characteristics in terms of competency achievement, students are able to understand the meaning and meaning of the Church in Phase F Class XI SMKN 3 Magelang in the 2023/2024 academic year. This type of research is Classroom Action Research using 2 cycles. With research variables learning motivation, critical reasoning and Problem Based Learning techniques. The population of students who are Catholics at SMK Negeri 3 Magelang. The sample of class XI students is Catholic with a total of 4 students. Data collection techniques in this study were observation and questionnaires. Cycle 1 motivation obtained the highest interest questionnaire score of 27 on behalf of Chornelia in the competent category, the lowest score of 15 on behalf of Agatha was included in the appropriate category. If seen from the average interest score of 20.5 in cycle 1, this is included in the proficient category. Attention in cycle 1 gets an overview of the highest score of 26 on behalf of Chornelia including the proficient category, the lowest score on behalf of 15 Agatha is included in the appropriate category. The average attention score of 20.3 in cycle 1 is included in the proficient category. Meanwhile, the highest participation score of 25 on behalf of Cornelia is in the competent category, while the lowest score of 16 is in the appropriate category. The average participation score of 20.3 is included in the proficient category.The results of the study show that the percentage of motivation in cycle 1 is only 51% of the motivation that appears in learning, so it needs to be increased again so that learning objectives are achieved. Critical reasoning ability Cycle 1 obtained the highest critical reasoning questionnaire score of 22 on behalf of Chornelia included in the proficient category, the lowest score of 8 on behalf of Agatha was included in the appropriate category. If seen from the average score, a score of 14 is included in the feasible category. So it is necessary to increase the ability of critical reasoning so that learning objectives can be achieved optimally. The percentage of critical reasoning abilities shows that the ability of students has only reached 50%, so there is also a need for improvement so that learning objectives can be achieved optimally. Furthermore, cycle 2 motivation obtained the highest interest questionnaire score of 37 on behalf of Cornelia included in the proficient category, the lowest score of 19 on behalf of Agatha was included in the appropriate category. If seen from the average interest score of 29.8 in cycle 2, this is included in the proficient category. Attention in cycle 2 gets an overview of the highest score of 34 on behalf of Chornelia including the proficient category, the lowest score on behalf of 19 Agatha is included in the appropriate category. The average attention score of 28.3 in cycle 1 is included in the proficient category. While the highest participation score of 34 on behalf of Cornelia is in the proficient category, the lowest score is 21 in the proficient category. The average participation score of 27.8 is included in the proficient category. The percentage of critical reasoning abilities in cycle 2 can be seen that only 78% of students have motivation that appears in learning, already showing an increase in achieving learning goals. The final conclusion is that the use of the PBL model in teaching Catholicism in Church material for class XI SMKN 3 Magelang can increase motivation and critical thinking skills.